Renal Transplants from Older Deceased Donors: Use of Preimplantation Biopsy and Differential Allocation to Dual or Single Kidney Transplant according to Histological Score Has No Advantages over Allocation to Single Kidney Transplant by Simple Clinical Indication - Costanza Casati; Valeriana Giuseppina Colombo; Marialuisa Perrino; Ornella Marina Rossetti; Marialuisa Querques; Alessandro Giacomoni; Agnese Binaggia; Giacomo Colussi (Journal of Transplantation)
Background. Grafts from elderly donors (ECD) are increasingly allocated to single (SKT) or dual (DKT) kidney transplantation according to biopsy score. Indications and benefits of either procedure lack universal agreement. Methods. A total of 302 ECD-transplants in period from Jan 1, 2000, to Dec 31, 2015, were allocated to SKT (SKTpre) on clinical grounds alone (before Dec 2010, pre-DKT era, n=170) or according to a clinical-histological protocol (after Dec 2010, DKT era, n=132) to DKT (n=48), SKT biopsy-based protocol (“high-risk”, SKThr, n=51), or SKT clinically based protocol (“low-risk”, SKTlr, n=33). Graft and patient survival were compared between the two periods and between different transplant categories. Results. Graft and overall survival in recipients from ECD in pre-DKT and DKT era did not differ (5-year graft survival 87.7% and 84.2%, resp.); equal survival in the 2 ECD periods was shown in both donor age ranges of 60–69 and >70-years, and in low-risk or high-risk ECD categories. Within the DKT protocol SKThr showed worst graft and overall survival in the 60–69 donor age range; DKT did not result in significantly better outcome than SKT from ECD in either era. One-year posttransplant creatinine clearance in recipients did not differ between any ECD transplant category. At 3 and 5 years after transplantation there were significantly higher total dialysis-free recipient life years from an equal donor number in the pre-DKT era than in the DKT protocol. Conclusions. Use of a biopsy-based protocol to allocate grafts from aged donors to SKT or DKT did not result in better short term graft survival than a clinically based protocol with allocation only to SKT and reduced overall recipient dialysis-free life years in time.